Methane recovery from natural gas hydrate with simulated IGCC syngas - Ding, Ya-Long; Xu, Chun-Gang; Yu, Yi-Song; Li, Xiao-Sen (Energy, 2017)
Methane(CH4) recovery from natural gas hydrates(NGHs) by CO2-CH4 replacement is considered as a win-win technology for producing CH4 and sequestrating CO2 synchronously. In this investigation, simulated Integrated Gasification Combined Cycle (IGCC) syngas of CO2/H-2 gas mixture is used to replace CH4 from simulated methane hydrate which is formed in pure water at 274.15 K and 4.5 MPa. The changes of concentrations of CH4, CO2 and H-2 in gas phase during the replacement process are supervised by Gas Chromatograph (GC), and the gas hydrates are determined through in situ Raman. Meanwhile, the CH4 recovery and the replacement mechanism are qualitatively analyzed. The results indicate that, on one hand, the replacement consists of two steps, CH4 hydrate dissociation at the first and followed by CO2 hydrate formation, on the other hand, the CH4 recovery from CH4-CO2/H-2 replacement is more than 71% which is significantly higher than that from CH4-CO2 replacement. Notably, no H-2 is found in the hydrate phase in the replacement process, which implying that H-2 does not compete with CH4 molecules occupying hydrate cages but plays promotion role in CO2-CH4 replacement.(C) 2017 Elsevier Ltd. All rights reserved.